Evolution of geomembrane degradation and defects in a landfill: Impacts on long-term leachate leakage and groundwater quality. (1st July 2019) - Sun, Xiao-chen; Xu, Ya; Liu, Yu-qiang; Nai, Chang-xin; Dong, Lu; Liu, Jing-cai; Huang, Qi-fei
Abstract: Due to the performance degradation of liner systems, landfill leachate may significantly increase over the long term, and ignorance of this may lead to a serious underestimation of a landfill's emissions and associated environmental impact during its life cycle. This paper examined the long-term behavior of HDPE geomembranes under field conditions using analytical and mechanical tests as well as the geoelectric leak location method. The aging information obtained, together with site-specific meteorological and hydrogeological data and landfill design parameters, were then used in the LandSim and HELP models to perform quantitative analyses of leachate production, emission, and environmental impacts on groundwater. The results demonstrated that the HDPE geomembranes reaches its service life after 8 years of landfill operation, beyond which its hydraulic performance begins to degrade rapidly. This results in leachate leakage increasing from an initial level of 0.05–0.6 m 3 /d to a long-term range of 27.4–37.6 m 3 /d. This is accompanied by changes to its impact on groundwater, with the impact extent expanding from 50 to 1000 m and pollution probability going from "almost impossible" to "almost certain". The above results remind us to take measures to control the aging process of HDPE geomembranes in landfill environments in order to extend their service life. Moreover, it also suggests that we should consider the long-term emissions of landfills as well as the impact of secondary waste disposal when conducting landfill life cycle assessment. Highlights: HDPE GM life in filed condition is 10–300 times shorter than that expected ideally. Results in a drastic increase in leachate leakage from 0.05 to 0.6 to 27.4–37.6 m 3 /d. Indicates emissions in its EOL accounting for a large proportion in its life cycle.